Perbandingan Efektivitas Pendidikan Kesehatan terhadap Pengetahuan dan Kemampuan Ibu Merawat Balita ISPA di Puskesmas Padang Pasir dan Pauh - Dwi Novrianda; Henny Lucida; Irfandy Soumariris (Jurnal Sains Farmasi & Klinis, 2015)
Health education with booklet media is an effort to increase knowledge and ability in caring Acute respiratory infection (ARI). This study aimed to identify comparison effectivity in health education towards knowledge and ability in caring between Padang Pasir and Pauh Health Center. Method used pre experimental with pretest posttest design. Subject was mothers with children having ARI amount 15 samples. Data was collected by questionnaires. Data analysis used wilcoxon to identify difference pre and posttest of mother’s knowledge and ability in caring, mann whitney-U to know difference between both of them. Study showed there was difference of knowledge and ability in caring between pre and posttest (p=0,002). There was difference in effectivity of health education between Padang Pasir and Pauh on ability in caring (p=0,004).It suggested health education with more interesting media like booklet must be given especially for mothers so ARI’s rate can be reduced in children.